Sympathy–Antipathy in Daniel Deronda - Carolyn Burdett (19, 2020)
This article argues that, in her final novel, Daniel Deronda, Eliot uses her eponymous protagonist to simultaneously exemplify and problematize the type of sympathy she had championed from the 1850s. Sympathetic affinity in the novel works like original ‘occult’ sympathy, irresistibly connecting non-adjacent things, and matched in its force by sympathy’s original twin, antipathy. The article investigates the novel’s antipathies, arguing that Eliot eschews meliorism and offers instead a brave glimpse into the obdurate forces of hatred and destructiveness that shadow our best selves.